Multilayer Network of Neuro-Fuzzy Units in Forecasting Applications - Bodyanskiy, Yevgeniy; Popov, Sergiy (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
A new neuron architecture named Neuro-Fuzzy Unit (NFU) is proposed, which is a generalization of elementary Rosenblatt's neuron and Neo-Fuzzy Neuron (NFN) by Yamakawa. NFU eliminates drawbacks of NFN, which complicate its application in multilayer networks. A learning algorithm based on gradient back-propagation procedure is introduced. The obtained results are confirmed by networks comparison in the task of short-term forecasting of electric load time series.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 9-14